Day of Surgery Admission in Total Joint Arthroplasty: Why Are Surgeries Cancelled? An Analysis of 3195 Planned Procedures and 114 Cancellations - David M. Dalton; Enda G. Kelly; Terence P. Murphy; Gerry F. McCoy; Aaron A. Glynn (Advances in Orthopedics)
Background. Day of surgery admission (DOSA) is becoming standard practice as a means of reducing cost in total joint arthroplasty. Aims. The aim of our study was to audit the use of DOSA in a specialty hospital and identify reasons for cancellation. Methods. A retrospective study of patients presenting for hip or knee arthroplasty between 2008 and 2013 was performed. All patients were assessed at the preoperative assessment clinic (PAC). Results. Of 3195 patients deemed fit for surgery, 114 patients (3.5%) had their surgery cancelled. Ninety-two cancellations (80%) were due to the patient being deemed medically unsuitable for surgery by the anaesthetist. Cardiac disease was the most common reason for cancellation (n=27), followed by pulmonary disease (n=22). 77 patients (67.5%) had their operation rescheduled and successfully performed in our institution at a later date. Conclusion. DOSA is associated with a low rate of cancellations on the day of surgery. Patients with cardiorespiratory comorbidities are at greatest risk of cancellation.